Integration of Copperas and Moringa oleifera Seeds as Hybrid Coagulant for Turbidity and Ammonia Removal from Aquaculture Wastewater - Sofiah Hamzah; Nazaitulshila Rasit; Nurul Aqilah Mohamad; Mohammad Hakim Che Harun; Alyza Azzura Abd Rahman Azmi; Nur Hanis Hayati Hairom; Ahmad Ariff Fahmi Mustofa; Mohd Salleh Amri Zahid; Norhafiza Ilyana Yatim; Nor Azman Kasan (Indonesian Journal of Chemistry, 2023)
The rapid development of the aquaculture industry has contributed to the high amount of nutrients in wastewater that subsequently led to eutrophication and deterioration of water quality. Aquaculture wastewater consists of uneaten fish feed, fecal and other excretion or residue of chemicals used. Thus, this study aimed to evaluate the performance of hybrid coagulants of Moringa oleifera (MO) and copperas for aquaculture wastewater treatment. In this present study, different formulations of MO and copperas were explored in the coagulation treatment of aquaculture wastewater using a jar test experiment. The FTIR and SEM analysis are used to determine the morphology and surface of MO. This study focuses on the effect of coagulant aids formulation, coagulant dosage, the effect of initial pH and coagulation time on turbidity and ammonia removal in the coagulation of aquaculture wastewater. The finding shows that the highest removal of turbidity and ammonia was obtained with the use of 80% MO and 20% copperas at the condition of initial pH of 6 at 20 min of coagulation time, with the highest percentage removal of 66% and 91%, respectively. The coagulation isotherm of hybrid coagulant 80:20 is well described with the Freundlich isotherm model which describes the surface heterogeneity.